Religious Translation between Arabic and English, with Reference to Quranic Rhetorical Questions - Najjar, Ibrahim; Kadhim, Kais Amir (Respectus Philologicus, 2021)
Translating rhetorical questions from one language into another is not an easy task at all. This is due to the fact that rhetorical questions are not posed to elicit information, but rather to denote something else, namely rhetorical functions or purposes. Such functions might be changed and or distorted in translation if certain issues are not considered. Of these issues is the tenor of rhetorical questions. As such, the current study is an attempt to investigate Quranic rhetorical questions that denote rhetorical functions such as negation, testing, and showing abundance to determine the extent to which the tenor of such questions is preserved in the English translation of al-Hilali and Khan (1996). Toward this end, the interpersonal metafunction of the Quranic rhetorical questions and their English translation is analysed. In this case, the study employs Halliday's (1996) tenor and its associated metafunction, i.e., interpersonal metafunction. The analysis shows that the tenor of Quranic rhetorical questions under investigation is maintained, highly distorted and partially distorted. Consequently, the functions of such rhetorical questions are mostly affected.